Mercificazione e strumentalizzazione dei simboli religiosi nello stato laico (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Fattore religioso e società multiculturale: alla ricerca di uno spazio giuridico dai contorni flessibili - 3. Crisi della rappresentanza e “resilienza laica” - 4. La politica a favore (o contro) i simboli e la funzione dello stato laico - 5. Uso patologico dei simboli religiosi e nuove “mappe giuridiche” (… oltre il diritto pattizio) - 6. Conclusioni.Commodification and instrumentalization of religious symbols in the secular StateABSTRACT: The article deals with religious symbols and their use in the public and legal sphere by political actors. Following some recent events, the author shows that the (mis)use of symbols in political life generates disorientation in both social and electoral dynamics. Such (mis)use is also relevant to positive and secular law, insofar this latter is called to regain its natural flexibility, to meet new needs of individuals and collective formations, induced by social changes of multicultural society.